Synthesis of Arts: Conceptions, Forms, and Meaning - Stoškus, Krescencijus (Problemos, 1983)
Since Romanticism a tradition has been preserved to consider the synthesis of arts as a phenomenon increasing the possibilities of differentiated arts and contributing to overcoming one-sidedness of man in contemporary society. Different versions of the above theory (conceptions by F. W. Schelling, R. Wagner, etc.) are considered in the article. According to the view grounded by the author, the synthesis (integration) of arts is only one of the aspects of the functioning of art. In the history of art development, depending on aesthetic ideals and aspirations of the society, this aspect may turn into a dominating tendency and be opposed to the process of differentiation.